Purification and characterization of a heme-containing amine dehydrogenase from Pseudomonas putida. - Durham, D R (1978)
The primary amine dehydrogenase of Pseudomonas putida NP was purified to homogeneity as judged by polyacrylamide gel electrophoresis. Cytochrome c or an artificial electron acceptor was required for amine dehydrogenase activity. The enzyme was nonspecific, readily oxidizing primary monoamines, benzylamine, and tyramine; little or no measurable activity was detected with isoamines, L-ornithine, L-lysine, and certain diamines or polyamines. The pH optima for n-butylamine, benzylamine, and n-propylamine were 7.0, 6.5, and 7.0, respectively. The molecular weight of the enzyme was 112,000 as determined by gel filtration and 95,300 as analyzed by sedimentation equilibrium. Subunit analysis by sodium dodecyl sulfate gel electrophoresis suggested that the enzyme was composed of two nonidentical subunits with molecular weights of 58,000 and 42,000. The absorption spectrum of the purified enzyme was indicative of a hemoprotein, exhibiting absorption maxima at 277, 355, and 408 nm. Reduction with sodium dithionite or amine substrates resulted in absorption maxima at 523 and 552 nm and a shift in the Soret peak to 416 nm. These results suggested that the enzyme is a hemoprotein of the type c cytochrome. There was no evidence that flavins were present.